“We all see things through a different lens based on our life experiences”: co-production of a web-based implementation toolkit with stakeholders across the health and social care system - Brooks, Cindy Faith; Lund, Susi; Kryl, David; Lloyd Jones, Sian; Myall, Michelle (Frontiers in Health Services, 2024)
Background Implementing new innovations across the health and social care system is complex, involving many factors that in recent years have been compounded by Covid-19. While a plethora of implementation tools and frameworks are available, there are limitations in terms of their design and accessibility. Co-production is a valuable mechanism for developing tools that have utility and accessibility for those tasked with using them in health and social care organisations and there is growing acknowledgement of increasing the role of co-production in implementation science. This paper provides novel insight into co-production practices and relevance to implementation science by reporting findings from a study to co-produce a web-based implementation toolkit (WIT) that is accessible, usable and designed to support adaptive implementation across health and social care systems. Key themes relating to the process of co-production are outlined and the value of using co-production in implementation processes are discussed. Methods A web-based survey (n = 36) was conducted with a range of stakeholders across health and social care. Findings identified a need for WIT. Survey respondents were invited to express interest in becoming part of a co-production group and to take part in three online interactive workshops to co-produce WIT. Workshops took place with the group (n = 12) and focused on key developmental stages of WIT. Results Online co-production workshops were integral to the development and refinement of WIT. Benefits of using this process identified three interrelated themes: (i) Co-designing key features of the toolkit, (ii) Co-producing a toolkit with utility for users across health and social care settings, (iii) Co-producing a toolkit to support the implementation journey. Our approach of undertaking co-production as a dialogic process enabled generation of these themes. To illuminate discussion of these themes we draw upon iterative co-development of the “active ingredients” of key components (e.g., interactive Implementation Wheel) and functions (e.g., interactive “pop-up” definitions of keyword) and features (e.g., case studies) of WIT. Conclusion Using a co-production approach with a range of end-users across health and social care systems, highlights the benefits of understanding implementation processes for users in these settings. User-centred design and processes for ensuring accessibility readily support the translation of implementation into rapidly changing health and social care systems to benefit outcomes for patients, their families, carers, service users and practitioners.